Factors affecting the level of educated unemployment in the city of Pekanbaru - Andrel Rosevelt; Rahmita Budiartiningsih; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research conducted in the city of pekanbaru. The alm to determine the factor that influence the level of educated unemployment in pekanbaru city in 2011.As for the data used in the study is primary data and secondary data, The data analysis method used in this researh is descriptive method. The population in this researhare those who have completed their undergraduate education S1 with a population of educated unemployment in 2011 as many as 6.284 people and the sampling conducted asmany as 98 respondent accidental sampling.From the analysis of data obtained the researh that the factors affect the level of educated unemployment in pekanbaru city in 2011 amounted to 38,77% respondent said lack of jobs, 37,75% respondent said salaries offened are not satis factory or not as expected, And only 23,46% of respondent said in compatibility education expertise with jobs offers.Of the total sample, showed that the matority of educated unemployment are employed because of the limited field of work that is equal to 38,77%.Keyword : Employetment opportunities, Wages, Skill or education